A randomized controlled trial of group CBT with positive psychotherapy intervention for university students with maladaptive perfectionism in China - Zuo, Zhijuan; Zhang, Xingli (Frontiers in Psychology, 2023)
The negative influence of maladaptive perfectionism in university students with Asian cultural backgrounds is becoming increasingly notable. Objective: The primary objective of this randomized controlled trial was to find a more economical and feasible intervention for maladaptive perfectionism, which is a risk and maintenance mechanism of various psychopathologies. Methods: Sixty-four university students who met the total inclusion criteria were randomly assigned to group CBT with positive psychotherapy intervention or a 16-week wait list (WL). The intervention group received two hours of therapy for eight weekly sessions. Measurements for maladaptive perfectionism and the symptoms of depression and anxiety were conducted at baseline, post-intervention and follow-up. Results: There was no statistically significant difference in the scores of the Frost Multidimensional Perfectionism Scale, Self-rating Depression Scale and Self-rating Anxiety Scale between the intervention group and the waitlist group at baseline (all P>0.05). The intervention group had a significant main effect of time and a time×group interaction effect of maladaptive aspects of perfectionism, Concern over Mistakes, Doubts about Actions, depression and anxiety scores in comparison with the waitlist group at the post-intervention and 8-week follow-up and had no statistically significant effects on the scores of Personal Standards, Parental Expectation and Parental Criticism. The analysis showed that group intervention reduced symptoms of depression and anxiety while reducing maladaptive aspects of perfectionism. Conclusion: This study added to the literature on CBT interventions for maladaptive perfectionism and indicated that group CBT with positive psychotherapy intervention had substantial long-term effects on the maladaptive perfectionism of university students in China. Moreover, the results indicated that the intervention increased participants' self-acceptance.